2017
DOI: 10.1002/1873-3468.12756
|View full text |Cite
|
Sign up to set email alerts
|

Collision coupling in the GABAB receptor–G protein–GIRK signaling cascade

Abstract: The signaling cascade comprising the 4‐aminobutyrate(B) receptor (GABABR), G protein and the G protein‐gated K+ channel (GIRK) mediates neuronal inhibition in the brain. Precoupling between components of the pathway (within a permanent macromolecular complex) has been proposed, but this remains debatable. We investigated this mechanism in Xenopus oocytes by varying the expression of the GABABR. Increased expression of GABABR accelerates activation of GIRK by agonist, implying that some of the components in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Our results show that the increase in the amount of mRNA of M2R per oocyte (i.e., increase in surface density) speeds up the activation of GIRK1/2 ( Figure 1A, red plot-mono-exponential fit from which we extract t act ), with a corresponding decrease in the time constant of activation ( Figure 1B). These results are consistent with those obtained for M2R-G z -GIRK and GABA B R-G i/o -GIRK cascades in this heterologous model (Vorobiov et al, 2000;Kahanovitch et al, 2017).…”
Section: Collision Coupling Between M2r and G I/o In Girk Cascade In supporting
confidence: 92%
See 2 more Smart Citations
“…Our results show that the increase in the amount of mRNA of M2R per oocyte (i.e., increase in surface density) speeds up the activation of GIRK1/2 ( Figure 1A, red plot-mono-exponential fit from which we extract t act ), with a corresponding decrease in the time constant of activation ( Figure 1B). These results are consistent with those obtained for M2R-G z -GIRK and GABA B R-G i/o -GIRK cascades in this heterologous model (Vorobiov et al, 2000;Kahanovitch et al, 2017).…”
Section: Collision Coupling Between M2r and G I/o In Girk Cascade In supporting
confidence: 92%
“…In previous publications, we presented evidence for catalytic collision coupling between M2R and Gα z ( Vorobiov et al, 2000 ) and GABA B receptors with endogenous or coexpressed Gα i/o ( Kahanovitch et al, 2017 ) in the GPCR-G protein-GIRK cascade reconstituted in Xenopus oocytes. To examine whether this is also the case for the M2R-G i/o -GIRK cascade, and for the following quantitative description and kinetic modeling of the cascade, we first characterized the mode of M2R-G i/o coupling using our previously developed strategy ( Vorobiov et al, 2000 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…5 A ) and had no effect on its magnitude (Table 3, rows a and h). It is widely agreed that GABA B receptors are mediated by GIRK channels (Kahanovitch et al, 2017), including in GnRH neurons (Zhang et al, 2009). Thus, the effect of TPNQ was tested on the inhibition triggered by the activation of GABA B receptor.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the OFQ inhibition to Cs and Ba, but not to TPNQ, naringin, or ML297, indicated a different subunit composition of the GIRK channels associated with ORL1 (Kobayashi et al, 2011) in GnRH cells and suggested the presence of GIRK2 subunits in their GIRK channels. To further test this hypothesis, baclofen, a GABA B agonist, was used to activate GIRK channels (Kahanovitch et al, 2017). Although GABA B can use two-pore domain potassium channels (Bushell et al, 2002; Deng et al, 2009), the literature supports the role of GABA B using inwardly rectifying potassium currents in GnRH neurons (Wagner et al, 1998; Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%